Improvement of water slot design for beam blank casting mould. (1st November 2013) - Luo, W; Yan, B; Lu, X; Wen, G H
Abstract : Two-dimensional thermo-elastic-plastic creep finite element models of two beam blank moulds with different water slot designs, the large hole mould and the small hole mould, are set up and their thermomechanical behaviour is numerically investigated by means of ABAQUS software. The temperature, distortion, stress and inelastic strain range across the hot faces as well as the fatigue life of the two moulds are discussed in detail, based on which it is shown that the distributions of temperature and distortion of the small hole mould are more uniform than those of the large hole mould, and the peak temperature of the former mould is smaller than that of the later mould. However, the fatigue life of the small hole mould is shorter than that of the large hole mould. Both moulds were put into service in an industry and it is demonstrated that the quality of the product cast by the small hole mould is better than that by the large hole mould, and the service life of the small hole mould is longer than that of the large hole mould because the service life of a mould chiefly depends on the wear of its hot face, which is much shorter than the fatigue life. An improved water slot design for the beam blank mould is then proposed and it is numerically demonstrated that this improved mould is superior to the large hole mould and the small hole mould.